Through a glass darkly : the social sciences look at the neoliberal university - Thornton, Margaret (Margaret Rose) (ANU Press, 2014)
This collection of essays arose from a workshop held in Canberra in 2013 under the auspices of the Academy of Social Sciences in Australia to consider the impact of the encroachment of the market on public universities.